THE EFFECT OF BRAND IMAGE AND QUALITY SERVICE ON SAVING DECISIONS WITH COMPETITIVE ADVANTAGE AS AN INTERVENING VARIABLE AT BANK DKI MAYOR BRANCH, EAST JAKARTA - Matondang, Friska Novelina; Wahyuni, Dr. Sri (jfpublisher, 2023)
Nowadays, business competition is getting more stringent, therefore a competitive strategy is needed that companies must have to survive in this business competition, especially banks in an effort to increase the number of customers. Therefore, this research was conducted to analyze the effect of brand image and quality service on saving decisions with competitive advantage as an intervening variable at Bank DKI Mayor Branch, East Jakarta. The population in this research is customers who open accounts at Bank DKI Mayor Branch, East Jakarta. The data collection method uses a survey method by filling out a questionnaire. Data analysis using the SEM (Structural Equation Modeling) software application with the AMOS program. The results of this research obtained the following results: (1) brand image has a positive and significant effect on purchasing decisions; (2) brand image has a positive and significant effect on competitive advantage; (3) service quality has a positive and significant effect on purchasing decisions; (4) service quality has a positive and significant effect on competitive advantage; and (5) purchasing decisions have a positive and significant effect on competitive advantage.